Peralihan Bahan Bakar Cofiring Batubara - Biomassa untuk Mengurangi Dampak Lingkungan: Studi Kasus PLTU Bukit Asam, Sumatera Selatan - Widanti, Feraliza; Boedoyo, M. Sidik; Murtiana, Sri (UNIB Press, 2025)
This study explores the implementation of coal and biomass co-firing at the Bukit Asam Power Plant in South Sumatra as a strategy to reduce the environmental impact of coal usage. Indonesia's coal resources are estimated to reach 104 billion tons, with domestic production in 2010 amounting to 240 million tons. The majority of coal is used for electricity generation, but global demand has experienced fluctuations, with declines in developed countries but significant growth in Asian countries. Coal, as a fossil fuel, has negative impacts on health and the environment, prompting the search for cleaner solutions like co-firing. Co-firing is the process of burning a mixture of coal and biomass, aimed at reducing greenhouse gas and pollutant emissions. The Bukit Asam Power Plant utilizes various types of biomass, such as rice husks and palm oil waste, with the appropriate biomass ratio for operational efficiency. This research shows that co-firing can significantly reduce CO₂, SO₂, and NOₓ emissions, as well as provide local economic benefits by empowering communities through biomass utilization. These findings are relevant to Indonesia's energy and environmental policies, supporting the transition towards more sustainable energy, and providing recommendations for policymakers in developing climate change mitigation strategies in the energy sector.